2017
DOI: 10.7554/elife.22199
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology derived source-sink mechanism of BMP gradient formation

Abstract: A morphogen gradient of Bone Morphogenetic Protein (BMP) signaling patterns the dorsoventral embryonic axis of vertebrates and invertebrates. The prevailing view in vertebrates for BMP gradient formation is through a counter-gradient of BMP antagonists, often along with ligand shuttling to generate peak signaling levels. To delineate the mechanism in zebrafish, we precisely quantified the BMP activity gradient in wild-type and mutant embryos and combined these data with a mathematical model-based computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
130
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
2
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(141 citation statements)
references
References 93 publications
11
130
0
Order By: Relevance
“…We also note the gradually declining expression of grem2b: a secreted dorsal Bmp signaling inhibitor, which is upregulated by both Edn1 and Jag/Notch, and downregulated by Bmp signaling . These results add a new level of temporal complexity to our computational models for the zebrafish D-V arch GRN (Clouthier et al, 2010;Meinecke et al, 2018) similar to models in other patterning systems (Pomreinke et al, 2017;Sagner & Briscoe, 2017;Zinski et al, 2017) particularly for processes involving multiple signals in concert (Zagorski et al, 2017). Testing how combinatorial signals lead to such temporal expression kinetics will require experimental manipulation of morphogen gradients at specific times and locations such as with heat-shock inducible transgenic constructs Zuniga et al, 2011).…”
Section: Temporal Expression Profiles Of Mouse Arch Patterning Genementioning
confidence: 70%
See 1 more Smart Citation
“…We also note the gradually declining expression of grem2b: a secreted dorsal Bmp signaling inhibitor, which is upregulated by both Edn1 and Jag/Notch, and downregulated by Bmp signaling . These results add a new level of temporal complexity to our computational models for the zebrafish D-V arch GRN (Clouthier et al, 2010;Meinecke et al, 2018) similar to models in other patterning systems (Pomreinke et al, 2017;Sagner & Briscoe, 2017;Zinski et al, 2017) particularly for processes involving multiple signals in concert (Zagorski et al, 2017). Testing how combinatorial signals lead to such temporal expression kinetics will require experimental manipulation of morphogen gradients at specific times and locations such as with heat-shock inducible transgenic constructs Zuniga et al, 2011).…”
Section: Temporal Expression Profiles Of Mouse Arch Patterning Genementioning
confidence: 70%
“…Examples include the interaction of Bmp and Shh signaling in D-V neural tube patterning (Liem, Jessell, & Briscoe, 2000;Zagorski et al, 2017) and the interaction of Wnt, retinoic acid (RA) and Fgf signaling in A-P body axis patterning (McGrew, Hoppler, & Moon, 1997;White, Nie, Lander, & Schilling, 2007). Measurements of morphogen diffusion and immediate downstream target genes, combined with computational modeling, have clarified which of several alternative models of signaling are applicable, such as a source-sink model for early embryonic patterning in zebrafish by the Bmp pathway (Pomreinke et al, 2017;Zinski et al, 2017). Precise measurements of target gene expression, such as those in the Nodal signaling pathway, have also suggested that in some morphogen systems the kinetics of expression are more important than more classical threshold models for proper patterning (Dubrulle et al, 2015).…”
mentioning
confidence: 99%
“…Morphogens near the local source get attached to the shuttle and the morphogen‐shuttle complex is transported across tissues. Subsequently, the morphogen‐shuttle complex is degraded, resulting in the morphogen being immobilized to stationary negative diffusion regulators and formation of a gradient …”
Section: Parallels Between Neurotransmission and Morphogen‐based Tranmentioning
confidence: 99%
“…Subsequently, the morphogen-shuttle complex is degraded, resulting in the morphogen being immobilized to stationary negative diffusion regulators and formation of a gradient. 52,60 Beyond extracellular-diffusion-based morphogen transport, several studies suggest that morphogens also can be transported through cell-based mechanisms via transcytosis or along cellular extensions known as cytonemes. [61][62][63] In the case of transcytosis, signaling molecules are taken up by cells through endocytosis and subsequently released through exocytosis into the extracellular space.…”
Section: Parallels Between Neurotransmission and Morphogen-based Trmentioning
confidence: 99%
“…Example geometries and a time-lapse of a single solution are shown in Figure 2A. To test the Partial Differential Equation (PDE)-based models developed herein, we used the previously published point cloud data for P-Smad5 (readout of BMP signaling) that is available online at Zinski et al (Zinski et al 2017). To apply these data to our model, we processed the data by fitting the original data to a standard size hemisphere with different levels of coverage along the elevation direction based on the embryonic stage of development.…”
Section: Measurement Of Source Distributionsmentioning
confidence: 99%